Development of Teaching Materials for Dialogue Training: Drama Script Containing The Value of Madura Local Tradition for Class XI High School Students - Irna Rinawatul Fitriyah; Didin Widyartono; Indra Suherjanto (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2025)
This study aims to describe the development of Dialogue Exercise materials: Drama Scripts Containing Local Madurese Traditional Values. The data collection techniques employed in this study included interviews and questionnaires. The results of this study show the development of teaching materials for Dialogue Exercises: Drama Scripts Containing Local Madurese Traditional Values in the form of teaching material validation results. The assessment results of teaching material validators indicate that the teaching materials have very valid teaching material validity, very valid material presentation, valid Language, valid design, and appearance. The presentation of the research results revealed that 92% of teaching material experts, 84% of material presentation experts, 71.43% of Language, and 76.6% of design and appearance are by the objectives of the research indicators. The validation results given by two learning practitioners showed 97.5%. The results were obtained from the assessment criteria indicators that met excellent aspects. The validation results, as provided by 30 students, showed a success rate of 85%. The percentage obtained is based on criteria such as (1) communicative, (2) dialogic and interactive, (3) language compatibility with PUEBI, and (4) attractive appearance according to the needs of students. These results indicate that the teaching materials meet perfect criteria. This study concludes that the teaching materials Dialogue Exercises: Drama Scripts Containing Local Madurese Traditional Values ​​provide essential contributions, both theoretically and practically, to the development of science in the field of education, especially in the development of media and teaching materials based on local culture.